Systemic protection through remote ischemic preconditioning is spread by platelet‐dependent signaling in mice. Issue 4 (13th August 2014) - Oberkofler, Christian E.; Limani, Perparim; Jang, Jae‐Hwi; Rickenbacher, Andreas; Lehmann, Kuno; Raptis, Dimitri A.; Ungethuem, Udo; Tian, Yinghua; Grabliauskaite, Kamile; Humar, Rok; Graf, Rolf; Humar, Bostjan; et al.
<x xml:space="preserve">Abstract</x> Remote ischemic preconditioning (RIPC), the repetitive transient mechanical obstruction of vessels at a limb remote to the operative site, is a novel strategy to mitigate distant organ injury associated with surgery. In the clinic, RIPC has demonstrated efficacy in protecting various organs against ischemia reperfusion (IR), but a common mechanism underlying the systemic protection has not been identified. Here, we reasoned that protection may rely on adaptive physiological reponses toward local stress, as is incurred through RIPC. Standardized mouse models of partial hepatic IR and of RIPC to the femoral vascular bundle were applied. The roles of platelets, peripheral serotonin, and circulating vascular endothelial growth factor (Vegf) were studied in thrombocytopenic mice, Tph1−/− mice, and through neutralizing antibodies, respectively. Models of interleukin‐10 (Il10) and matrix metalloproteinase 8 (Mmp8) deficiency were used to assess downstream effectors of organ protection. The protection against hepatic IR through RIPC was dependent on platelet‐derived serotonin. Downstream of serotonin, systemic protection was spread through up‐regulation of circulating Vegf. Both RIPC and serotonin‐Vegf induced differential gene expression in target organs, with Il10 and Mmp8 displaying consistent up‐regulation across all organs investigated. Concerted inhibition of both molecules abolished the protective effects of RIPC. RIPC was able to mitigate pancreatitis, indicating that it can protect beyond ischemic insults. Conclusions: We have identified a platelet‐serotonin‐Vegf‐Il10/Mmp8 axis that mediates the protective effects of RIPC. The systemic action, the conservation of RIPC effects among mice and humans, and the protection beyond ischemic insults suggest that the platelet‐dependent axis has evolved as a preemptive response to local stress, priming the body against impending harm. (Hepatology 2014;60:1409–1417)